The effects of temperature and pH on the dissolution and passivation processes of copper in carbonate-bicarbonate solutions - Ribotta,S.B. (1997)
Electrochemical studies of polycrystalline copper electrodes in carbonate-bicarbonate solutions analyzing both temperature and pH effects were carried out, covering a wide range of electrolyte composition in the 5-65 °C range. Hydrodynamic conditions were also considered. The results are explained on the basis of a modification of the characteristics of the film through solution stirring and high temperature. In this situation, a less hydrated passive layer is obtained, reducing the dissolution process. The ionic strength becomes an additional factor that affects the general state of the system.